Total Phenolic Content of Ethanol Extract of Artrocarpus camansi Leave and its Effect to SOD (Superoxide Dismutase) Level in Mice - Hendri Asrin; Poppy Anjelisa Zaitun Hasibuan; Marianne Marianne (Indonesian Society for Cancer Chemoprevention, 2017)
A free radical is one of the triggers of degenerative diseases that become the biggest cause of death. Excessive production of free radicals can be neutralized by antioxidant. Antioxidants can be generated from within the body (intracellular). One of them by the enzyme SOD (superoxide dismutase). However, when the production of free radicals exceeds the ability of intracellular antioxidants to neutralize it, antioxidants from outside (extracellular) is necessary. The ethanol extract of Artocarpus camansi leaves (EEACL) contains phenolic compounds which has very strong antioxidant activity based on in vitro study using the DPPH method, but the in vivo study about the total phenolic content effect of its leaves toward antioxidant activity has not been done. 25 mice were divided into 5 groups consisting of control group, a group was induced by stress and three groups were induced by stress, but given EEACL with each dose of 50 mg/kg bw, 100 mg/kg bw and 150 mg/kg bw. Inducing stress in the form of psychological stress was carried out for 7 days and continued with the EEACL administration for 7 days. The mice were dissected and the livers were isolated, then the liver morphological was examined using Hematoxyllin Eosin (HE) staining method and SOD level was examined with immunohistochemical staining method. The data were analyzed with One Way ANOVA and Duncan test using SPSS program version 19.0. Total phenolic content of EEACL is 235.03 ± 4.306 mg GAE/ g of sample. The average SOD levels in the control group is 94.05 %, stressed group is 55.94 %, stress with EEACL dose 50 mg/kg bw group is 58.40 %, stress with EEACL dose 100 mg/kg bw group is 79.68 %, stress with EEACL dose 150 mg/kg bw group is 80.90 %. Based on statistical result, SOD level increased along with the increase of EEACL dose, but not significantly (p < 0,05). Total phenolic content of EEACL has an influence to SOD levels. SOD level increased along with the increase of EEACL administration dose. The higher dose of EEACL leading to higher levels of SOD in the mouse liver.Keywords : total phenolic content, superoxide dismutase, antioxidant, Artocarpus camansi